Peering beyond the monotypic veil: taxonomy and notes on the parental care of Neocranaus (Opiliones: Gonyleptoidea: Cranaidae) - Villarreal, Osvaldo; González-Gómez, Julio César; Kury, Adriano B.; García, Luis Fernando (European Journal of Taxonomy, 2024)
The genus Neocranaus Roewer, 1913 is revisited, its composition is expanded from two to five species and a new generic diagnosis is presented. Neocranaus albiconspersus Roewer, 1913, type species of the genus, is redescribed. The genus Tolimaius Roewer, 1915 syn. nov. is considered as a junior subjective synonym of Neocranaus, its sole member being transferred to Neocranaus – N. pectinitibialis (Roewer, 1915) comb. nov. – and redescribed here. The new combination Neocranaus laevifrons (Roewer, 1917) comb. nov. is proposed for Holocranaus laevifrons Roewer, 1917. The new species Neocranaus gladius Villarreal & Kury sp. nov. is described, from P.N.N. Yariguíes, Santander Department, Colombia. For the first time, the genital structure of this genus is illustrated. A key to the identification of the males of Neocranaus and some considerations about the reproductive biology of N. albiconspersus and N. pectinitibialis are presented.